Bullying Victimization, Gender, and Adolescent Substance Use: The Moderating Role of School Connectedness - Lehmann, Peter S. (Crime & delinquency, 2025)
A substantial body of research has demonstrated that bullying victimization is positively associated with illicit substance use, though whether this relationship is stronger among female or male youth remains unclear. Additionally, while connectedness to school represents a robust protective factor against negative health and behavioral outcomes, limited research has examined if it might weaken the effect of victimization on substance use. Analyses of data from the 2022 Florida Youth Substance Abuse Survey (N = 47,572) reveal that bullying victimization is positively related to substance use, especially among female adolescents. Unexpectedly, this positive effect of victimization on substance use is found to be stronger among youth with higher levels of school connectedness, and this latter relationship does not vary by gender.